Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To work out the gradient of each line, let's follow a step-by-step process for each equation.
### Finding the Gradient of the Line [tex]\( y = 5x - 3 \)[/tex]
1. Identify the form of the equation:
- The given equation is [tex]\( y = 5x - 3 \)[/tex].
- This is in the slope-intercept form, [tex]\( y = mx + c \)[/tex], where [tex]\( m \)[/tex] is the gradient.
2. Determine the gradient:
- By comparing [tex]\( y = 5x - 3 \)[/tex] to [tex]\( y = mx + c \)[/tex], we see that [tex]\( m = 5 \)[/tex].
Therefore, the gradient of the line [tex]\( y = 5x - 3 \)[/tex] is [tex]\( 5 \)[/tex].
### Finding the Gradient of the Line [tex]\( 3y - 12x + 7 = 0 \)[/tex]
1. Rearrange the equation into the slope-intercept form:
- Start with [tex]\( 3y - 12x + 7 = 0 \)[/tex].
- Add [tex]\( 12x \)[/tex] to both sides: [tex]\( 3y = 12x - 7 \)[/tex].
- Divide by 3: [tex]\( y = 4x - \frac{7}{3} \)[/tex].
2. Identify the gradient:
- The equation is now in the form [tex]\( y = mx + c \)[/tex], where [tex]\( m \)[/tex] is the gradient.
- Here, [tex]\( m = 4 \)[/tex].
Therefore, the gradient of the line [tex]\( 3y - 12x + 7 = 0 \)[/tex] is [tex]\( 4 \)[/tex].
Summarizing the gradients:
- The gradient of the line [tex]\( y = 5x - 3 \)[/tex] is [tex]\( 5 \)[/tex].
- The gradient of the line [tex]\( 3y - 12x + 7 = 0 \)[/tex] is [tex]\( 4 \)[/tex].
### Finding the Gradient of the Line [tex]\( y = 5x - 3 \)[/tex]
1. Identify the form of the equation:
- The given equation is [tex]\( y = 5x - 3 \)[/tex].
- This is in the slope-intercept form, [tex]\( y = mx + c \)[/tex], where [tex]\( m \)[/tex] is the gradient.
2. Determine the gradient:
- By comparing [tex]\( y = 5x - 3 \)[/tex] to [tex]\( y = mx + c \)[/tex], we see that [tex]\( m = 5 \)[/tex].
Therefore, the gradient of the line [tex]\( y = 5x - 3 \)[/tex] is [tex]\( 5 \)[/tex].
### Finding the Gradient of the Line [tex]\( 3y - 12x + 7 = 0 \)[/tex]
1. Rearrange the equation into the slope-intercept form:
- Start with [tex]\( 3y - 12x + 7 = 0 \)[/tex].
- Add [tex]\( 12x \)[/tex] to both sides: [tex]\( 3y = 12x - 7 \)[/tex].
- Divide by 3: [tex]\( y = 4x - \frac{7}{3} \)[/tex].
2. Identify the gradient:
- The equation is now in the form [tex]\( y = mx + c \)[/tex], where [tex]\( m \)[/tex] is the gradient.
- Here, [tex]\( m = 4 \)[/tex].
Therefore, the gradient of the line [tex]\( 3y - 12x + 7 = 0 \)[/tex] is [tex]\( 4 \)[/tex].
Summarizing the gradients:
- The gradient of the line [tex]\( y = 5x - 3 \)[/tex] is [tex]\( 5 \)[/tex].
- The gradient of the line [tex]\( 3y - 12x + 7 = 0 \)[/tex] is [tex]\( 4 \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.